2014
DOI: 10.1111/vcp.12152
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic and immunocytochemical characterization of feline progressive histiocytosis

Abstract: FPH is a distinctive neoplastic lesion composed of nonphagocytizing histiocytes variably admixed with neutrophils and small mature lymphocytes. Immunocytochemical analysis with CD1 is mandatory to confirm a dendritic cell origin. Immunocytochemistry and cytomorphology allowed the specific and rapid diagnosis of FPH on cytologic samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 33 publications
(102 reference statements)
0
41
1
2
Order By: Relevance
“…This cat is disease‐free (follow‐up, 465 days). It may be that in this case immune‐mediated mechanisms are involved, as in reactive histiocytosis in dogs, or a Langherans tumour, behaving like canine histiocytoma: testing for E‐cadherin was negative, however, variable expression of this marker has been found in two different studies on FPH …”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…This cat is disease‐free (follow‐up, 465 days). It may be that in this case immune‐mediated mechanisms are involved, as in reactive histiocytosis in dogs, or a Langherans tumour, behaving like canine histiocytoma: testing for E‐cadherin was negative, however, variable expression of this marker has been found in two different studies on FPH …”
Section: Discussionmentioning
confidence: 81%
“…A recent study on FPH using immunocytochemistry (ICC) reported that neoplastic cells expressed CD1a, CD1c, CD11b, CD18 and MHCII . CD1 was needed to confirm a dendritic cell origin, but this marker is of limited use on formalin fixed samples . In contrast to previous studies, E‐cadherin expression was reported in 4 out of 5 cats with FPH at presentation.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Those antibodies were proven to be specific to the feline antigen. A previous report showed the specificity of anti-feline CD18 monoclonal antibody and anti-human CD3 polyclonal antibody [ 22 ]. The specificities of the remaining antibodies were tested by IHC with normal feline lymph node (data not shown).…”
mentioning
confidence: 99%